Pelatihan Penulisan Proposal PTK Bagi Guru MGMP Bahasa Indoensia SMP di Kabupaten Maros - Abdul Haliq; Anshari; Sakaria; Asis Nojeng (Jurnal Pengabdian Masyarakat, 2023)
One of the demands of professional teachers is their competence in the field of classroom action research. The reality on the ground shows that the classroom action research that has been prepared has not shown the CAR that is as expected. The solution that can be done to overcome this is to conduct training on writing class action research proposals (CAR). This activity has an output target in the form of a PTK proposal framework. The target partner in this community service activity is the Indonesian language MGMP for the Middle School in Maros district. The implementation of activities with a follow-up study design will be described in the methods of lectures, questions and answers, assignments, discussions, and practice/simulation as well as evaluation. The benchmark for achieving the goal is that participants can absorb at least 80% of the material provided by the presenters (IbM implementers) in preparing PTK proposals, both theory and practice. The results of the implementation of this activity showed that the participants had been able to develop PTK proposals in accordance with the problems they faced in their schools, especially in learning Indonesian. Thus, it is no longer difficult for teachers to conduct classroom action research. The evaluation results show that this community service activity is categorized as very good (90%) in terms of the participants' activeness and motivation. Meanwhile, in terms of understanding and learning practices produced are categorized as good (80%).